Politeness Strategies among EFL Learners: A Literature Review - Damar Isti Pratiwi; Novita Eka Tristiana; Ainun Fikria (UICELL, 2022)
Many studies have been conducted on politeness strategies employed by EFL learners in social communication or classroom contexts. As a result, it is fascinating to analyze the extent to which scholars have explored this issue. By examining 20 published articles in reputable journals in a decade (2011 – 2021), this literature review study aimed to investigate the politeness strategies employed among EFL learners and the pedagogical implications of politeness strategies in EFL classrooms. The findings showed that there were five politeness strategies used in social communication, including positive politeness, bald on-record, negative politeness, off-record, and do not do FTA. Nonetheless, the latest strategy was not employed in the classroom context. Each strategy chosen by EFL learners was due to the power, social distance, age, and cultural background. These findings shed light on the pedagogical implication of politeness strategies, which should be implied in the teaching learning process and in designing the course and preparing the materials. Keywords: Politeness, Politeness Strategies, EFL Learners, Pragmatics, Literature Review